THE MODERATING EFFECT OF BUSINESS GROWTH ON FINANCIAL INCLUSION AND SMES SUSTAINABILITY: EMPIRICAL EVIDENCE FROM NORTH CENTRAL NIGERIA - Ogedengbe, Frank Alaba; Almakura, Faisal Ahmed; Gambo, Nasamu (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study investigates the moderating role of business growth in the relationship between financial inclusion and Small and Medium Enterprise (SME) sustainability in North Central Nigeria. Using a cross-sectional survey design, data were collected from 544 SME owners and managers across seven states and the Federal Capital Territory. Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed to test hypotheses regarding six financial inclusion dimensions—financial literacy, inclusive credit scoring, consumer protection, insurance uptake, affordable banking services, and banking diversity—and their effects on operational efficiency, with business growth as a moderator. The results reveal that banking diversity (β = 0.518, p < 0.001) and business growth (β = 0.435, p < 0.001) are the strongest predictors of operational efficiency, explaining 78% of the variance (R² = 0.780). Consumer protection demonstrated a modest positive effect (β = 0.172), while financial literacy, inclusive credit scoring, insurance uptake, and affordable banking services showed negligible or negative effects. Moderation analysis indicated that business growth positively amplifies the effects of consumer protection and insurance uptake but diminishes the influence of financial literacy and credit scoring. These findings challenge conventional assumptions about the universal benefits of financial inclusion and underscore the need for growth-sensitive, context-specific financial strategies. Theoretical and practical implications are discussed.